Risk Evaluation and Information Security Protection in the Implementation of Management Information Systems - Rahma Intan Nuraini; Muhammad Irwan Padli Nasution (Young Journal of Social Sciences and Humanities, 2025)
Data is one of the asset important and valuable Good for individual and organization . In the System Information Management (SIM), stored data can in the form of financial data , customer data, employee data , and important data others . Therefore that , data security in SIM is very important For protect information from threat like data theft , damage physique to system information and threats other . Articles This aim For discuss about data security in SIM, risks that can occur occurs in data security , and protection strategies that can be done For overcome risk said . Data security in system information management is effort For protect , secure asset information from possible threats​ will arise that can endanger confidentiality , availability , and integrity all asset information company , not only device hard and soft , but also the sensitive data stored on it Data security in System Information Management is critical aspects​ For every organization . Risk data security can originate from various sources and their impacts can be very serious . Practical suggestions For overcome risk data security in SIM , namely Cyber Security Topics, Awareness Employees , Security Solutions Network , Plan Data Recovery , Compliance Audits , and Evaluations Periodic .